2016
DOI: 10.1155/2016/9085273
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Analysis of the Cytokine and Anhedonia Response to Peripheral Lipopolysaccharide Administration in Rats

Abstract: Inflammatory processes may cause depression in subsets of vulnerable individuals. Inflammation-associated behavioral changes are commonly modelled in rodents by administration of bacterial lipopolysaccharide (LPS). However, the time frame in which immune activation and depressive-like behavior occur is not very clear. In this study, we showed that systemic administration of LPS robustly increased circulating levels of corticosterone, leptin, pro- and anti-inflammatory cytokines, and chemokines. Serum concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
19
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 42 publications
4
19
1
Order By: Relevance
“…The magnitude of the decrease of plasma cytokines levels seen in this study was greater than that found in the above studies but this may be due to the higher level of LPS (2 mg/kg) used in the study as compared to the lower levels used in the other studies (0.03 mg/kg in [Abramova et al, 2013], 0.6 mg/kg in [Fischer et al, 2015]). In contrast to the other cytokines, we found that the level of IL-10 showed a significant increase in the LPS injected rats at 24 h. This increase in IL-10 was not found in the other rat studies which used low levels of LPS [Abramova et al, 2013;Fischer et al, 2015;Biesmans et al, 2016]. In contrast, the result in our study for IL-10 is consistent with the response seen in mice but only when a similarly high level of LPS was used (3 mg/kg in [Erickson and Banks, 2011], 2.5 mg/kg [Biesmans et al, 2013]) and not when a lower level of LPS was used (0.6 mg/kg [Biesmans et al, 2013]).…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…The magnitude of the decrease of plasma cytokines levels seen in this study was greater than that found in the above studies but this may be due to the higher level of LPS (2 mg/kg) used in the study as compared to the lower levels used in the other studies (0.03 mg/kg in [Abramova et al, 2013], 0.6 mg/kg in [Fischer et al, 2015]). In contrast to the other cytokines, we found that the level of IL-10 showed a significant increase in the LPS injected rats at 24 h. This increase in IL-10 was not found in the other rat studies which used low levels of LPS [Abramova et al, 2013;Fischer et al, 2015;Biesmans et al, 2016]. In contrast, the result in our study for IL-10 is consistent with the response seen in mice but only when a similarly high level of LPS was used (3 mg/kg in [Erickson and Banks, 2011], 2.5 mg/kg [Biesmans et al, 2013]) and not when a lower level of LPS was used (0.6 mg/kg [Biesmans et al, 2013]).…”
Section: Discussioncontrasting
confidence: 75%
“…We then investigated the effect of the LPS challenge on the levels of 12 different cytokines in the plasma. In response to an LPS injection in rodents (in particular mice) there is a rapid increase in the levels of cytokines in the plasma with the levels peaking between 2 and 6 h after LPS injection and for most cytokines there is a decrease to basal levels by 24 h [Erickson and Banks, 2011;Biesmans et al, 2013;Biesmans et al, 2016]. In contrast, our study found that at 24 h after LPS injection the majority of the cytokines (IL-1a, IL-1b, IL-2, IL-4, IL-5, IL-6, IL-12(p70), IL-13, GM-CSF, IFN-g, TNF-a) showed a very significant decrease in plasma compared to the control.…”
Section: Discussionmentioning
confidence: 99%
“…This effect is modest and although not repeated in the second behavioural study, a trend for a similar effect was observed. This lack of robust anhedonic effects following LPS is likely due to the low dose of LPS used herein compared with previous studies (Biesmans et al, 2016;Sayd et al, 2015) and the confounding effect of prior surgery and icv vehicle administration. Despite this, the data suggest that FAAH inhibition may modulate immune-mediated anhedonia, a core symptom of psychiatric disorders such as depression.…”
Section: Discussionmentioning
confidence: 76%
“…Accumulating evidence has shown that both acute and chronic stress potentiated the sickness response to LPS administered 24 h post-stress [ 13 15 ]. In the present study, surgical trauma impaired spontaneous locomotor activities and increased the levels of anxiety in the adult rats.…”
Section: Discussionmentioning
confidence: 99%